Alkyl-functionalization of 3, 5-bis(2-pyridyl)-1, 2, 4, 6-thiatriazine. (25th January 2016) - Kleisath, Elizabeth; Yutronkie, Nathan J.; Korobkov, Ilia; Gabidullin, Bulat M.; Brusso, Jaclyn L.
Abstract : S -Alkyl-1, 2, 4, 6-thiatriazines, which can be prepared via two pathways, are described. The regioselectivity and photophysical properties are rationalized through computational studies. Abstract : A versatile synthetic route to prepare alkyl functionalized 3, 5-bis-(2-pyridyl)-1, 2, 4, 6-thiatriazines is described that can proceed either via cationic or anionic pathways; confirmed through characterization of the isolable intermediates. Computational studies are presented, which support the regioselectivity of the alkylation reactions and photophysical properties of the S -alkylated derivatives.